Hello!

The height of the first object is given by

`h1(t) = 60 - 10*t - (g*t^2)/2` ,

where 60 is the initial height, -10 is the initial downward speed and g is gravity acceleration, g=`9.8m/s^2` .

The height of the second object is

`h2(t) = 40t`

(I suppose its...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Hello!

The height of the first object is given by

`h1(t) = 60 - 10*t - (g*t^2)/2` ,

where 60 is the initial height, -10 is the initial downward speed and g is gravity acceleration, g=`9.8m/s^2` .

The height of the second object is

`h2(t) = 40t`

(I suppose its speed is assumed to be constant).

Note that t>=0. Objects pass each other when they have equal height, i.e. h1(t) = h2(t):

`60 - 10*t - (9.8*t^2)/2 = 40t` , or

`4.9*t^2 + 50*t - 60 = 0` .

The roots are ` ``t1,2 = (-50 +- sqrt(2500 + 4.9*240))/9.8 approx (-50 +- 60.63)/9.8` .

The root with "-" is <0, the only solution is t1 = 10.63/9.8 = 1.085 (s).

The heigth at t1 is 40*t1 = 40*1.085 = **43.4 (m)**.